Digital Marketing: Consumers’ Purchase Intention Towards E-commerce Platform for Urban Region - A. Mohd Ali; S. Manogaran; K. Selvarajan; N.I Tajuddin; M.R Mohd Johan; U. Munikrishnan (Tehran Urban Research & Planning Center: Tehran Municipality (TURPC)., 2024)
Indexed by Scopus